Hirtella L. (Chrysobalanaceae) para a flora da Bahia, Brasil - Pereira, Renata Camargo Asprino (2016)
This work presents the floristic survey and a taxonomic treatment of the genus Hirtella (Chrysobalanaceae) from the state of Bahia, Brazil (Chapter 2). The survey of the species was done through the consult of several herbaria collections,literature, and field work. It were found fourteen species of Hirtella in Bahia. The treatment includes an identification key, descriptions, comments on taxa, as well as ilustrations and geographic distribution maps of species in the state. During the development of the present work it was found a new species of Hirtella, which is described in Chapter 1. The new species is morphologically close to H. santosii, for which is provided a more detailed morphological description and new information about its distribution and habitat. In Chapter 3, is presented a palynological analysis of Hirtellaspeciesfrom the state of Bahia, which belongs to sect. Hirtella,and an amazonian species of the sect. Myrmecophila, for comparison. The results show that Hirtella pollen grains are of little taxonomic importance. Nevertheless, the present study shows new information about the ornamentation of the exine through scanning electron microscopy, contributing to increase the palynological knowledge in the group.